Supporting the National Action Plan on Nutrition : Estimating the Cost, Impact, Cost-Effectiveness, and Economic Benefits of Expanding the Coverage of Direct Nutrition Interventions in Bangladesh - Kakietek, Jakub; Provo, Anne; Mehta, Michelle; Sharmin, Farhana; Shekar, Meera (World Bank, Washington, DC, 2018)
In January 2016 the Government of Bangladesh requested technical assistance from the World Bank and the United Nations Children’s Fund (UNICEF) to estimate the cost of implementing nutrition actions considered for the inclusion in the country’s Second National Plan of Action for Nutrition (NPAN2) and to assist with the prioritization of scale up of the nutrition action over the coming 10 years. This report presents the analysis conducted as part of the technical assistance. It consists of four parts. Part I presents background context and an overview of nutritional status of the population of Bangladesh, with a focus on pregnant women and children under age five. Part II describes the methodology employed, including details on the assumptions used to develop unit costs (cost per beneficiary) that will be used by the Government of Bangladesh as the basis for estimating the cost of the implementation of the NPAN2. Part III presents an analysis of the costs, benefits, and cost-effectiveness of a set of key nutrition-specific interventions included in the NPAN2. Part IV of the report summarizes the main conclusions, limitations, and policy implications. The goal of the analysis is to contribute to the building of an investment case for nutrition in Bangladesh and to inform prioritization within the NPAN2 by identifying which interventions are the most cost-effective (that is, which offer the lowest cost per death averted or case of stunting averted) and in which geographic regions investments in nutrition-specific action have the potential to achieve the greatest impact.